Kompensasi, Tingkat Pendidikan, Moralitas dan Pengaruhnya Terhadap Perilaku Tidak Etis Sopir Bus Akap - Prayitno Prayitno (JBIMA (Jurnal Bisnis dan Manajemen), 2015)
This study aims to determine the effect of compensation, level of education and morality against unethical behavior, either partially or simultaneously. Method used in sampling purposive sampling, sampling is based on consideration for in accordance with the criteria in order to improve the accuracy of the sample. by criteria a driver who is experienced as a driver for at least 1 year. The analytical method used is multiple linear regression with a significant level (α) 0,05. The results of this study concluded that partial compensation does not affect unethical behavior, with significant value of 0,100 is less than 0,05. Partially education level does not affect unethical behavior, with significant value of 0,638 is more than 0,05. Suggestions to reduce unethical behavior of the driver, it is recommended to provide compensation remains as long as this has been done because no matter how much the compensation awarded to the driver can not reduce behavior unethical done by the bus driver. Suggestions for reducing transport entrepreneurs driver of unethical behavior, it is recommended to provide compensation remains as long as this has been done because no matter how much the compensation awarded to the driver can not reduce unethical behavior done by the bus driver.